(untitled) (Research, Society and Development, 2025)
To analyze the epidemiological profile of pulmonary and extrapulmonary tuberculosis in the five macro-regions of Brazil from 2015 to 2019. Specific objectives include describing the proportional frequency of cases per year, comparing regional differences, and identifying possible associations with socio-environmental factors. This is a retrospective, cross-sectional, and quantitative study based on tuberculosis records from the Brazilian Ministry of Health’s DataSUS system, specifically from the SINAN Net database, covering the years 2015 to 2019. Data were filtered by region and socio-environmental variables, including government beneficiaries, immigrants, alcoholism, and drug use. Statistical analysis was performed using Epi Info 7.0, with a significance level of p < 0.05.Between 2015 and 2019, 452,308 tuberculosis cases were recorded in Brazil. Alcoholism was the most significant socio-environmental factor associated with tuberculosis, especially in the Northeast, where it accounted for over 55% of cases. In the Southeast, drug use was also highly correlated with tuberculosis cases. The North region presented a higher disease frequency, while the Center-West had the lowest incidence. No statistically significant association was found between socio-environmental factors and tuberculosis occurrence. Tuberculosis remains a significant public health issue in Brazil, with its highest prevalence in the North region. Although socio-environmental factors such as alcoholism and drug use were predominant among cases, their statistical association with tuberculosis was not confirmed. Further research is needed to understand the persistent factors contributing to the disease’s high incidence.